Serum Derived Extracellular Vesicles Mediated Delivery of Synthetic miRNAs in Human Endothelial Cells - Tapparo, Marta; Pomatto, Margherita Alba Carlotta; Deregibus, Maria Chiara; Papadimitriou, Elli; Cavallari, Claudia; D’Antico, Sergio; Collino, Federica; Camussi, Giovanni (Frontiers in Molecular Biosciences, 2021)
Extracellular vesicles (EVs) have emerged in the last decades as a cell-to-cell communication mechanism. One of their mechanism of action is the direct delivery of their cargo, composed of bioactive molecules to target cells. Different methods (direct electroporation, cell transfection, chemical transfection) were developed to vehicle therapeutic molecules through EVs. However, most of these techniques presented some limitations such as EV disruption and aggregation. In the present study, we demonstrated that a direct temperature-controlled co-incubation of EVs with defined miRNAs is a stable method to deliver information to target cells without affecting EV constitutive content. We chose serum as an easy and abundant source of EVs applicable to autologous treatment after EV modification. Exogenous cel-miR-39 loaded on serum EVs was taken up by human endothelial cells, demonstrating an adequate miRNA loading efficacy based on the co-incubation method. Moreover, serum EV (SEVs) co-incubation with the angiomiR-126 (miR-126) enhanced their angiogenic properties in vitro by increasing the capacity to induce capillary-like structure formation of human endothelial cells. MiR-126 loaded EVs were shown to promote angiogenesis also in vivo, by stimulating mouse endothelial cells to invade Matrigel plugs and create more vessels with respect to the EV naive counterpart. When SEVs were loaded with miR-19b, an anti-angiogenic miRNA, they were able to reduce Vascular endothelial growth factors (VEGF) pro-angiogenic capacity, supporting the selective biological effect mediated by the carried miRNA. Lastly, we identified Annexin A2 (ANXA2) as one of the molecules involved in the exogenous RNA binding to serum EV surface, favouring miRNA delivery to target endothelial cells for potential therapeutic application.